(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the role and importance of health-improving gymnastics in strengthening the health of women in our country. The development of women’s sports has become a very urgent problem in recent years. The issues of our government’s efforts to raise our youth as spiritually mature and physically fit generations are highlighted, as one of the first laws of our state, "On Physical Education and Sports", and one of the first awards established in the sports system is the Order "For a Healthy Generation".